Electrode dependence in halide perovskite memories: resistive switching behaviours. (21st September 2022) - Thien, Gregory Soon How; Sarjidan, Mohd Arif Mohd; Talik, Noor Azrina; Goh, Boon Tong; Yap, Boon Kar; He, Zhicai; Chan, Kah-Yoong
Abstract : In halide perovskite resistive switching memories, the top electrode material influences resistive switching features such as bipolar and unipolar switching, multilayer, and write-once-read-many behaviour. Abstract : Halide perovskites (HPs) are widely employed in a variety of applications including optoelectronics, lasers, light-emitting diodes, and photovoltaics. As HPs are superb semiconductors with remarkable electronic and light absorption characteristics, global research into these materials is flourishing in various industries. Thus, memory devices have lately seen a growth in the usage of HPs as a next-generation candidate for high-performance memories. Nonetheless, understanding the impact of design structure on HP memories, such as electrode dependence in producing different resistive switching (RS) properties, is critical in optimizing the design process. This review describes the top electrode (TE) dependence of various materials in creating diverse RS memory behaviour. The disparities in all recently reported RS characteristics based on different TE materials are addressed and explored. Current electrode modification advances and techniques in HP RS devices are also discussed. Through this, the relevance and importance of electrode dependence in the design architecture of HP memories toward RS mechanisms are highlighted in this review work.